CYT387, a JAK-Specific Inhibitor Impedes Osteoclast Activity and Oophorectomy-Induced Osteoporosis via Modulating RANKL and ROS Signaling Pathways - Li, Jing; Liang, Jiamin; Wu, Liwei; Xu, Yang; Xiao, Chengxiang; Yang, Xue; Sun, Ran; Zhao, Jinmin; Xu, Jiake; Liu, Qian; Zhou, Bo (Frontiers in Pharmacology, 2022)
Osteoclasts are of hematopoietic lineage and have the ability to degrade mineralized bone tissues. Abnormalities in osteoclastic activity under certain pathological conditions are common in bone diseases such as osteoporosis, osteosclerosis, and arthritis. Although many kinds of drugs are currently used to treat osteoporosis, they have obvious adverse reactions and limitations. CYT387 is a new small-molecule Janus kinase (JAK) inhibitor involved in hematopoiesis, immune modulation, fertility, lactation, and embryonic development. However, it has remained unclear whether CYT387 functionally impacts osteoclast formation. Our study demonstrated through osteoclast formation assay in vitro, that the use of CYT387 is a potential drug candidate for treating osteoclast-associated bone disease. The effects of CYT387 on osteoclast formation, bone resorption, NFATc1 activation, and especially intracellular ROS levels were investigated in vitro. Further, we examined the preclinical prospects of CYT387 using an oophorectomy (OVX) mouse model of osteoporosis with its anti-osteoclast activity in vivo. On the whole, this study shows that CYT387 holds promise for treating osteoclast-related bone illnesses including osteoporosis.